مشروعية القرار الإداري في النظام العُماني والمصري: دراسة تحليلية مقارنة - حميد بن ناصر بن حمد الحجري
This study dealt with the legality principle of the administrative decision in the Omani and Egyptian legal systems, and sought to show the importance of this principle in establishing a state of institutions and law and protecting the rights and freedoms of individuals. Which received the attention of Omani legislation and comparative legislation, and the Sultanate of Oman was keen to activate it, and its judiciary worked to consolidate it through a lawsuit to review the administrative decision under an effective judiciary that enjoyed complete independence within a dual system from the beginning. Then the judicial system was transformed into a unified system, so the study aimed to know the impact This shift in the legitimacy of the administrative decision.the study has adopted the descriptive analytical approach by tracking and extrapolating the opinions of administrative jurists, analyzing legal rules and judicial principles, and using the comparative approach by addressing the judicial principles decided by the French Council of State, and then the rulings of the Egyptian and Omani administrative judiciary.The study reached several conclusions, the most important of which is that most of the theories related to the principle of legality are judicial theories of origin where their application is decided by the administrative judge. The dual judiciary represented the real activation of the control of the administrative judiciary until the application of the unified judicial system. The study has also shown that the decision enjoys the presumption of validity and enforceability when its addressees are notified, and it includes, in varying proportions, a degree of discretion, and a degree of restricted jurisdiction together. However, its pillars have five defects called the grounds for reviewing the administrative decision. Among the most important recommendations of the study is the need for the legislator to intervene to transfer the judicial theories related to the principle of legality, which suffers from a disruption in the application; to be more disciplined. Such recommendations have also established the importance of maximizing the role of the judge in controlling the legitimacy of the decision and freeing him from the control of legislative texts restricting his discretion.